The Path Analysis of Family Doctor's Gatekeeper Role in Shanghai, China: A Structural Equation Modeling (SEM) Approach. (April 2021) - Huang, Jiaoling; Wang, Luan; Liu, Shanshan; Zhang, Tao; Liu, Chengjun; Zhang, Yimin
Studies globally have provided substantial evidence that PHC could conduct doctor-visiting behaviors, control medical expense, and improve population health. This study aimed to map how family doctor (FD) in Shanghai achieved gate-keeper goals including health management, medical expense control, and conducting ordered doctor-visiting behavior. A total of 2754 and 1995 valid questionnaires were collected in 2013 and 2016 respectively in Shanghai. The data were analyzed using structural equation modeling (SEM). Invariance analysis was also performed for 2 waves of data. We found that the coefficient of cognition on health management (β5 = 0.26, P < .05) was larger than that of signing with FD (β4 = 0.06, P < .05). SEM model also showed that first-contact at community health service center (CHSC) had a positive effect on health management (β6 = 0.30, P < .05), and the latter also affected health management results positively (β8 = 0.39, P < .05), suggesting that the path for FD was through first-contact and health management. Besides, the gate-keeper role of medical expense control was significant through the first-contact (β10 = −0.12, P < .05) mediation rather than health management (β9 = 0.03, P > .05). The model fit was acceptable (RMSEA = 0.033). A "cognition-behavior-outcomes (health and medical expense)" path of FD's gate-keeper role was found. It is necessary to consolidate FD contracted services rather than reimbursement discount the latter of which is proved to be unsustainable.